Developing Physics Teaching Materials with the SETS Approach on the Kinetic Theory of Gases Topic to Improve Students' Scientific Literacy Skills - Mazda Rezki; Abdul Salam; Dewi Dewantara (Universitas Lambung Mangkurat, 2023)
Scientific literacy as a skill and competence must be possessed in physics learning. However, the ability to be literate has not been well-trained and has received insufficient attention in schools. This research aims to develop teaching materials that are valid, practical, and effective with the SETS approach to enhance the scientific literacy of students. This research uses the ADDIE model as a guideline in developing teaching materials. The research method used is a pre-experimental research trial with 36 students in the 11th grade of Science 2 class at SMAN 11 Banjarmasin. The results of the study show: (1) Physics teaching materials with the SETS approach are considered valid because the worksheets, lesson plans, and teaching materials, as well as the learning outcomes test, are categorized as very good; (2) Physics teaching materials with the SETS approach are considered practical because the implementation of teaching and learning activities is categorized as very good; (3) Physics teaching materials with the SETS approach are declared effective because the N-gain score for scientific literacy is 0.75 in the high category. Thus, physics teaching materials with the SETS approach to the kinetic theory of gases are considered suitable for use in teaching and learning activities to enhance students' scientific literacy because they meet the criteria of validity, practicality, and effectiveness. The results of this research are used as input for teachers and prospective teachers to choose physics teaching materials with the SETS approach on the topic of the kinetic theory of gases to enhance students' scientific literacy.